Challenged by academic social networks - Melo, Luiza Baptista; Sanches, Tatiana (Qualitative and Quantitative Methods in Libraries; Vol 9 No 1 (2020): March 2020 Issue, 2020)
This communication reveals the practices of teachers and researchers from the Faculties of Dental Medicine, Psychology and the Institute of Education on the issue of the visibility of scientific information in academic social networks and in institutional repositories. The data were obtained by analysing the profiles of professors and researchers in a professional social network, ResearchGate, crossed with the documents of the Institutional Repository of the University of Lisbon (Repositório.UL), related to the studied schools. Statistical methods and quantitative data were used to compare the behaviours of the teachers and the researchers concerning their preferences on scientific documents dissemination throughout the World Wide Web.